Phonetic and Semantic Developments of the NativeArmenian Word “Yerkin” in Polynesian Languages andArmenian - Stepanyan, L. G.
The close prototype of the native Armenian word yerkin “sky, heaven” is found in the Polynesian Rapanui, Maori, Mangareva, Tuamotu languages, as an archaism preserved in the Far Eastern islands such as the penultimate stress and the VSO structure of the sentence specific to Pre-ProtoArmenian. Continuing the examination of the parallels revealed in Armenian through the pan-Polynesian ragi (rangi) “sky” > Armenian ¯ergi, yerkin “sky”, this article presents more than 10 word parallels of the latter’s lagi (langi) and laani variants in Armenian. The regular phonetic developments and semantic changes they have undergone in Armenian are revealed. Thus, it turns out that all the variations of the Polynesian root rangi, langi, laani “sky” in Polynesian languages are present in Armenian, with numerous and diverse dual-plan (phonetic and semantic) developments and form a fairly large genealogical cluster.
Keywords: Armenian Language